1993
DOI: 10.2466/pms.1993.77.3.923
|View full text |Cite
|
Sign up to set email alerts
|

Vividness of Imagery and Creativity

Abstract: We evaluated the extent to which vividness of imagery is correlated with creativity in a sample of 1361 university students from different disciplines and assessed which sensory modalities of vividness of imagery best predicted creativity. Vividness of imagery was generally poorly correlated with creativity and, for all subjects combined, explained only about 2% of total variance in creativity. Promising directions for research are mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Empirically, however, the two are closely related. For example, imagining ability (Campos & González, 1993a, 1993bCampos & Perez, 1989;González, Campos, & Pérez, 1997;Juhasz, 1972), visual imagery (Arieti, 1976;Koestler, 1964;McKellar, 1957;Parrott & Strongman, 1985;Schmeidler, 1965), concrete imagery (Paivio, 1971(Paivio, , 1975, and vividness of imagery (Forisha, 1978;Khatena, 1975;Richardson, 1969;Shaw & DeMers, 1986) have all been shown to relate positively to creativity. Indeed, meta-analysis reveals that mental imagery is positively associated with performance on creative thinking tasks (LeBoutillier & Marks, 2003).…”
Section: Economicsmentioning
confidence: 99%
“…Empirically, however, the two are closely related. For example, imagining ability (Campos & González, 1993a, 1993bCampos & Perez, 1989;González, Campos, & Pérez, 1997;Juhasz, 1972), visual imagery (Arieti, 1976;Koestler, 1964;McKellar, 1957;Parrott & Strongman, 1985;Schmeidler, 1965), concrete imagery (Paivio, 1971(Paivio, , 1975, and vividness of imagery (Forisha, 1978;Khatena, 1975;Richardson, 1969;Shaw & DeMers, 1986) have all been shown to relate positively to creativity. Indeed, meta-analysis reveals that mental imagery is positively associated with performance on creative thinking tasks (LeBoutillier & Marks, 2003).…”
Section: Economicsmentioning
confidence: 99%
“…Hyman (1993) and Roskos-Ewoldsen (1993) have noted that individual differences may play a role in the ability to manipulate their images. Many studies have shown that people with better imagery abilities (such as vividness, manipulation, transformation of images), are more creative (Campos & Gonzalez, 1993,1995Forisha, 1983;Kaufmann, 1990;Flower & Garbin, 1989;Shepard, 1978).…”
mentioning
confidence: 99%
“…This approach is named the individual differences approach (LeBoutiller and Marks, 2003). Indeed, since the 1960s, several empirical studies (Campos and Gonzalez, 1993a, 1993bCampos and Perez, 1989;Durndell and Wetherick, 1976;Forisha, 1981;Gonzalez et al, 1997;Kathena, 1975aKathena, , 1975bLeBoutiller and Marks, 2003;Parrott and Strongman, 1985;Rhodes, 1981;Schmeidler, 1965;Shaw and Belmore, 1982;Shaw and DeMers, 1986) have tried to shed light on possible correlations between measures of individual capacities for mental imagery (measures of the disposition to produce and control live images) and measures of creativity (personality inventories and/or tests of creative attitude, tests of creative or divergent thinking). However, the correlations are often weak and the results, obtained exclusively from student populations, are at times divergent.…”
Section: The Link Between Mental Imagery and Creativitymentioning
confidence: 99%